Where Do Bots Come From? An Analysis of Bot Codes Shared on GitHub. - KOLLANYI, BENCE (International Journal of Communication (19328036), 2016)
An increasing amount of open source code is available on the Internet for quickly setting up and deploying bots on Twitter. This development of open-source Twitter bots signals the emergence of new political economies that redistribute agencies around technological actors, empowering both the writers of the bots and users who deploy a bot based on the shared code. However, we have no systematic knowledge about how these bots are produced or what role sharing and collaboration play in this process. This article examines the practice of writing and sharing bot codes on GitHub, currently the largest online code repository, by analyzing data about more than 4,000 public Twitter bot code repositories from 2008 to 2016. The data reveal an exponential growth in the number of Twitter bots and a strong dominance of U.S.-based bot developers. Based on data gathered from GitHub about the social aspect of programming on the platform, the article also discusses how developers collaborate and interact with one another on GitHub around bot codes.